An Information systems study on Philex Mining Corporation - Botuyan, Mary Jean; Mamutuk, Nattalie R.; Rivera, Mary Ruby; Saquing, Flordeliz (College of Engineering, 1993)
The Information System study is conducted at the Accounts Receivable (A/R) Section of the Accounting Department of Philex Mining Corporation. Four types of transaction are covered in the study, namely, the A/R Miscellaneous, the A/R Advances to be Accounted for, the A/R Staff and Employees, and the A/R Officers. These accounts are among the remaining areas to be computerized in the said section. It is therefore the aim of the study to come up with a structured and formal documentation of the present system to be used in the design of an effective computerized IS. The documentation of the present system is made possible by interviewing all A/R personnel involved in the above-mentioned transactions. The study also utilized IS tools like the Data Flow Diagrams, the Data Dictionary and the Transform Descriptions for the documentation and analysis of the current system and the design of the proposed system. The proposed system requires changes in the work methods and the coverage of machine boundary. The suggested work method will minimize the processing time in the preparation of the Journal Voucher (JV). Its validation does not require all the present signatories but ends with the signature of the chief accountant. Meanwhile, machine boundaries encompass almost all the processing activities. This involves the computerization of the general ledger (GL) posting with the requirement that the information from the JV serving as the basis for posting to the GL be standardized.